2020
DOI: 10.1111/mec.15666
|View full text |Cite
|
Sign up to set email alerts
|

The generalizability of water‐deficit on bacterial community composition; Site‐specific water‐availability predicts the bacterial community associated with coast redwood roots

Abstract: Climatic and environmental change are predicted to increase the frequency, severity, and duration of droughts, the effects of which will probably be further exacerbated by rising temperatures (Diffenbaugh et al., 2015). Unprecedented droughts have already taken tolls on ecosystems from the temperate forests of California to the tropical forests of the Amazon (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 59 publications
2
6
0
Order By: Relevance
“…It may be then that the genetic drivers of Firmicutes' response to fire are either less genetically complex or more genetically integral to that phylum while Actinobacteria's response may be genetically varied or require the conservation of a greater number of genetic pathways in order to successfully adapt to fire. Finally, as this study is among the first to comprehensively characterize the soil microbiome of the charismatic redwood-tanoak forests, we note a few similarities in our pre-fire soils with a recent bacterial study of coastal redwood roots which also showed the most abundant taxa as Bradyrhizobium and Rhodoplanes (Willing et al, 2020). Additionally, a study of the microbial composition of the coastal redwood's sister genus, the giant sequoia (Sequoiadendron giganteum), also showed domination by Bradyrhizobium and Sinobacteraceae sp.…”
Section: Discussionsupporting
confidence: 66%
“…It may be then that the genetic drivers of Firmicutes' response to fire are either less genetically complex or more genetically integral to that phylum while Actinobacteria's response may be genetically varied or require the conservation of a greater number of genetic pathways in order to successfully adapt to fire. Finally, as this study is among the first to comprehensively characterize the soil microbiome of the charismatic redwood-tanoak forests, we note a few similarities in our pre-fire soils with a recent bacterial study of coastal redwood roots which also showed the most abundant taxa as Bradyrhizobium and Rhodoplanes (Willing et al, 2020). Additionally, a study of the microbial composition of the coastal redwood's sister genus, the giant sequoia (Sequoiadendron giganteum), also showed domination by Bradyrhizobium and Sinobacteraceae sp.…”
Section: Discussionsupporting
confidence: 66%
“…Although both bacteria and fungi display strong species‐area relationships (Li et al, 2020; Peay et al, 2007), previous research has demonstrated that the underlying mechanisms determining these patterns differ for both groups, where water availability influences bacterial diversity and biogeography is often more correlated with patterns of fungal diversity (Li et al, 2020). In a previous study across the same sites, we found that water availability was a key factor in determining bacterial diversity and community composition (Willing et al, 2020). In contrast, here we show that biogeographic factors, including habitat fragmentation and redwood cover, are important determinants of soil fungal community structure and diversity, especially for symbiotrophic fungi, which could have important feedbacks for redwood cover or potential transitions to ectomycorrhizal‐dominated forest (Peay, 2018; Steidinger et al, 2019).…”
Section: Discussionmentioning
confidence: 76%
“…To test our hypothesis (H1), we used generalised‐dissimilarity modelling (GDM) to assess the strength of the relationship between fungal community structure and habitat cover/fragmentation compared with biogeographic and climatic factors and soil chemistry (Manion et al, 2018). GDM accounts for non‐linear fits of community dissimilarity (Bray–Curtis dissimilarity was used here) across individual environmental and geographic gradients within a single model; GDM has been previously used to model microbial community structure across different gradients (Daws et al, 2020; Glassman et al, 2017; Willing et al, 2020). The full models included geographic distance, redwood cover (percent of redwood cover in buffer zone), habitat fragmentation (EDG), actual evapotranspiration, precipitation, minimum and maximum annual temperatures, soil pH, climatic controls on rates of decomposition ( k ), and Simpson index of landscape diversity; see Supplementary Information for a further description, including determination of soil chemistry.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Shannon index increased in half irrigated plots. Likewise, Willing et al [48] reported that increasing water-availability across the coastal redwood range decreased bacterial species richness estimated as Shannon index, suggesting that the turnover in bacterial communities was most likely to be driven by species loss with increasing water-availability instead of species replacement. Under our experimental conditions, bacterial alpha diversity was higher than fungal alpha diversity in accordance with Liang et al [49], who suggested that bacteria probably played roles that were more pivotal than fungi in vineyard soils.…”
Section: Differential Responses Of Bacterial and Fungi Composition To Amf Inoculation And Irrigation Treatmentsmentioning
confidence: 99%